RAGAM HIAS BINATANG DALAM MEDALION - Kirno Kirno (Corak : Jurnal Seni Kriya, 2012)
Indian - Indonesia culture acculturation played a riddle which still debated until today. Indian culturalinfluence was strong in Central Java and inversely proportional to the area of East Java. At thetemple, the visual form change was easily found where the form of towering slender turned into fatand wide. The concentric form change to chtonis system, human decorations that look realistic styleturned into puppets as one of the characteristics of prehistoric cultures. Decorative variety ofmedallions as one of ornament in Induk Panataran Temple are a visual text that attempts to conveya message. Animal species diversity engraved in Decorative variety of medallions became anevidence of the local genius skills in blending and gathering the Indian cultural influences for thefuture. Keyword : Ornament, Medallion, Panataran Temple, Local Genius